2011
DOI: 10.1371/journal.pone.0029431
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Analytical Approaches Reveal Distinct Gene-Environment Interactions in Smokers and Non Smokers in Lung Cancer

Abstract: Complex disease such as cancer results from interactions of multiple genetic and environmental factors. Studying these factors singularly cannot explain the underlying pathogenetic mechanism of the disease. Multi-analytical approach, including logistic regression (LR), classification and regression tree (CART) and multifactor dimensionality reduction (MDR), was applied in 188 lung cancer cases and 290 controls to explore high order interactions among xenobiotic metabolizing genes and environmental risk factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 43 publications
0
36
1
Order By: Relevance
“…Both GSTM1 and GSTT1 gene exhibit an inherited homozygous deletion polymorphism (null genotype), which has been associated with the loss of enzymatic activity and increased vulnerability to cytogenetic damage (Norppa, 2004). As a result of decreased efficiency in protection against carcinogens, the individuals with homozygous deletion polymorphism are considered to be at an increased risk for malignancies (Hayes et al, 2005;Mcllwain et al, 2006;Singh et al, 2010;Ihsan et al, 2011). Many studies have been published on the association of CYP1A1 and GSTM1 polymorphisms and lung cancer susceptibility with inconsistent findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both GSTM1 and GSTT1 gene exhibit an inherited homozygous deletion polymorphism (null genotype), which has been associated with the loss of enzymatic activity and increased vulnerability to cytogenetic damage (Norppa, 2004). As a result of decreased efficiency in protection against carcinogens, the individuals with homozygous deletion polymorphism are considered to be at an increased risk for malignancies (Hayes et al, 2005;Mcllwain et al, 2006;Singh et al, 2010;Ihsan et al, 2011). Many studies have been published on the association of CYP1A1 and GSTM1 polymorphisms and lung cancer susceptibility with inconsistent findings.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have been published on the association of CYP1A1 and GSTM1 polymorphisms and lung cancer susceptibility with inconsistent findings. Some of the studies showed the relationship between the polymorphisms of GSTM1 and CYP1A1 Ile/Val genotype (Singh et al, 2010;Ihsan et al, 2011) but other results are contradictory (Le Marchand et al, 1998;London et al, 2000). However, some data of Chinese Han population (Shi et al, 2008) and little data on Mongolian population are still available.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, lung cancer is a complex multifactorial disease, which occurs by multiple gene-gene and multiple geneenvironment interplay, thus, the effect of single SNP and a single gene does not adequately represent lung cancer risk. 46,47 Therefore, our study examined multiple SNPs in different DNA repair pathways. The HapMap database can provide wide coverage of common variations.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 14 studies (Benhamou et al, 1998;Persson et al, 1999;London et al, 2000;To-Figueras et al, 2001;Wu et al, 2001;Yin et al, 2001;Cajas-Salazar et al, 2003;Gsur et al, 2003;Harms et al, 2004;Liang et al, 2004;Voho et al, 2006;Timofeeva et al, 2010;Ihsan et al, 2011;Tilak et al, 2011) that included full-text articles and complied with HWE demonstrated an association between the EPHX1 Tyr113His polymorphism and lung cancer (Table 1). Among the studies included, 2 included 2 ethnicity types (London et al, 2000;Wu et al, 2001), and the data was collected separately and served as independent studies in our meta-analyses.…”
Section: Characteristics Of Relevant Studiesmentioning
confidence: 99%